Voices of Latin America : social movements and the new activism - Gatehouse, Tom (Practical Action Publishing Ltd ; Latin America Bureau, 2019)
This volume tells the story of the major issues, conflicts, and campaigns for social justice in the region today, in the words of the protagonists of these movements themselves. Tom Gatehouse has assembled an unparalleled set of views and insights from the leaders and intellectuals of that movement.